Literature, History, and the Structures of Knowledge Accumulation: a Study of Eric Auerbach and Muhammad Abed Al-Jabri (The International Journal of Educational Sciences and Arts, 2024)
The research compares the perspectives of Eric Auerbach and Muhammad Abed al-Jabri on the relationship between literature and history, as well as the structures of knowledge accumulation. Auerbach criticized the way Europeans viewed literature and history, which led to the sanctification of an ideal image of ancient Greek civilization at the expense of the reality of the lower classes. He also criticized the principle of "separation of styles" in European literature, which neglected the social reality of the lower classes. On the other hand, Al-Jabri points out that Arab culture lacks a unified temporal framework that organizes the sequence of thought and knowledge, leading to a "missing link" in the Arab historical consciousness, unlike the European culture, which has a stable frame of reference for the history of its thought. Thus, the research addresses the impact of cognitive and literary structures on the reading of history and the formation of historical consciousness in both European and Arab cultures.
Keywords: Literature and History; Structures of Knowledge Accumulation; Eric Auerbach; Muhammad Abed Al-Jabri; Structuralism and Arab Culture; the Principle of "Separation of Styles"; Historical Consciousness; the Cognitive Frame of Reference; the Missing Link in Arab Culture; the Formation of the Ideal Image of Greek Civilization